Novel fusion transcripts in bladder cancer identified by RNA-seq. Issue 2 (1st May 2016) - Kekeeva, T.; Tanas, A.; Kanygina, A.; Alexeev, D.; Shikeeva, A.; Zavalishina, L.; Andreeva, Y.; Frank, G.A.; Zaletaev, D.
Highlights: Four novel fusion transcripts were revealed by RNA-seq and validated in bladder cancer. Fusion transcripts SEPT9/CYHR, IGF1R/TTC23 and CASZ1/DFFA are rare events. SYT8/TNNI2 read-through transcript is a common bladder cancer event occurring in 37.5% of UC. Abstract: Urothelial carcinoma (UC) is the most common type of bladder cancer and is the second most frequently diagnosed genitourinary tumor. The identification of fusion genes in bladder cancer might provide new perspectives for its classification and significance. In this study, we present a thorough search on three UC samples for novel fusion transcripts in bladder cancer using high-throughput RNA sequencing. We used stringent requirements for 819 fusion candidates and nominated 10 candidate fusion transcripts. Among them four novel fusion genes SEPT9/CYHR, IGF1R/TTC23, SYT8/TNNI2 and CASZ1/DFFA were validated and characterized in 48 formalin-fixed paraffin-embedded (FFPE) specimens of bladder cancer . Chromosomal rearrangements of regions 17q25, 15q26.3 and 1p36.22 resulting in the fusion transcripts SEPT9/CYHR, IGF1R/TTC23 and CASZ1/DFFA, appeared to be rare or unique events because they were not detected in the 48 UC samples. In contrast, the SYT8/TNNI2 fusion transcript resulting from transcription-induced chimerism by read-through mechanisms was a rather common and tumor-specific event occurring in 37.5% (18/48) of the UC specimens. Further investigation of functional and clinical relevance of novel fusion genes remains to be elucidated to reveal their role in bladder carcinogenesis.